Determinants of financial risk tolerance: Evidence from the Indonesian millennials - Suherman Suherman; Herni Kurniawati; Rosle Mohidin (Conscientia Beam, 2023)
The purpose of this study is to examine the level of Indonesian millennials’ financial risk tolerance and the effect of gender, family occupation background, geographical location and financial literacy on financial risk tolerance. This research applies a quantitative approach using primary data that were collected through questionnaires. The sample used for this survey comprises 410 university students from western (Java, Sumatra, Kalimantan) and eastern (Bali, Nusa Tenggara, Sulawesi, Maluku, Papua) parts of Indonesia. The online survey was distributed to various universities in Indonesia. The one-way ANOVA and multiple regression methods were used for the analysis. The results show that: 1) the level of Indonesian millennials’ risk tolerance is moderate, 2) the level of Indonesian millennials’ financial risk tolerance is different, 3) gender, geographical location and financial literacy significantly affect the financial risk tolerance, and 4) family occupation background does not significantly affect the financial risk tolerance. These findings offer managerial insights into business practices in the financial industry to develop individualized investment portfolios based on investors’ financial risk tolerance. In addition, financial advisors are recommended to offer relatively riskier financial products to millennials from West Indonesia and those with higher financial literacy.